The Development of a Collegiate Recovery Program: Applying Social Cognitive Theory within a Social Ecological Framework. Issue 4 (4th July 2017) - Beeson, Eric T.; Whitney, Jennifer M.; Peterson, Holly M.
ABSTRACT: Background : Collegiate recovery programs (CRPs) are emerging as a strategy to provide after-care support to students in recovery from substance use disorders (SUDs) at institutions of higher education. CRPs are an innovative strategy for Health Educators to support the personal, academic, and professional goals of students in recovery.Purpose : This article reviews the history and current standards of CRPs as well as provides a case study on the development of a CRP at the University of North Carolina at Greensboro (UNCG).Translation to Health Education Practice : The early outcomes of CRPs are promising, and the case study presented in this article provides Certified Health Education Specialists with a model to guide the creation of additional CRPs.